Effect of dietary Moringa oleifera leaf meal supplementation on egg production and quality in village chickens - Ahmad, Nursalwani (2017)
A study was conducted to determine if any inclusion of different levels of Moringa oleifera leaf meal (MOLM) supplement into basal diet have an effect on the village feed intake, egg production and egg quality. Four treatment were used which are T1 (0% MOLM; Control), T2 (2.5% MOLM), T3 (5% MOLM) and T4 (7.5% MOLM). A total of thirty six hens of village chicken at 50 weeks of age were used. The hens were randomly allocated into four treatment group and every treatment has 3 replicates and every replicate consist of three hens. Complete randomized design (CRD) was used for the treatment which lasted for 5 weeks which one week for adaptation period and four weeks of collection data. Feed intake, weekly egg production, egg weights, external egg quality (shell thickness), internal egg quality (albumen height and egg yolk color) were determined. Eggs from each treatment were recorded on daily basis for measurement on egg production. Sampling of eggs were done randomly twice a week throughout experimental period, and used for measuring the quality traits. Eggs were randomly selected from each treatment twice a week for egg quality traits measurement. Data were collected on external and internal egg quality and also egg production for every week throughout the experiment. The increase in MOLM levels had no effect on feed intake, and egg weights (P>0.05). The result showed that birds on inclusion of 7.5% MOLM performed significantly (P<0.05) better in terms of egg production and egg quality. There was significant difference in egg yolk color score between the eggs from 7.5% MOLM (T4) diets and control treatment (T1). Except for shell thickness were not significantly affected (P>0.05) by the inclusion levels of MOL in the diet. For the egg weight are significantly (P<0.05) decreased with the increasing levels of MOLM. It was concluded in the conditions of this study that using Moringa oleifera leaves meal at 7.5% in the diet as feed supplement are recommended which can improves egg production and egg quality in village hens.